TINGKAT KESEGARAN JASMANI SISWA KELAS V SDN 011 AIR EMAS KECAMATAN SINGINGI - Dadang Setiawani; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, This research was motivated by some of the problems found in the field of which there are students of class V SDN 011 Air Emas District of Singingi some students have a level of physical fitness is not good enough, it is evident from the lack of enthusiasm for learning and the decline in learning results obtained by students. It is suspected of physical fitness was instrumental in improving learning outcomes, with good physical fitness students' learning difficulties will be overcome. The purpose of this study was to determine the level of physical fitness Student Class V SDN 011 Air Emas District of Singingi. The sample in this study is a female students totaling 28 people with sampling techniques using the total sampling. This research is a descriptive study, the data that has been collected and analyzed descriptively compiled to quantitatively. As for the formulation of the problem between is "What is the level of physical fitness Student Class V SDN 011 Air Emas District of Singingi?". From the research results can be concluded that the recapitulation Student Test Results Physical Fitness female students Class V SDN 011 Air Emas District of Singingi with the criteria very well and well not exist. While the criteria for being there 4 students or 14.3%. In less criteria as much as 8 people or by 28.57%, while on the criteria very less as many as 16 people or 57.1%.Keywords : Physical Fitnees